Screening in brief intervention trials targeting excessive drinkers in general practice: systematic review and meta-analysis. Issue 7414 (4th September 2003) - Beich, Anders; Thorsen, Thorkil; Rollnick, Stephen
Abstract: Objective To determine the effectiveness of programmes of screening in general practice for excessive alcohol use and providing brief interventions. Design Systematic review and meta-analysis of randomised controlled trials that used screening as a precursor to brief intervention. Setting General practice. Main outcome measures Number needed to treat, proportion of patients positive on screening, proportion given brief interventions, and effect of screening. Results The eight studies included for meta-analysis all used health questionnaires for screening, and the brief interventions included feedback, information, and advice. The studies contained several sources of bias that might lead to overestimates of the effects of intervention. External validity was compromised because typically three out of four people identified by screening as excessive users of alcohol did not qualify for the intervention after a secondary assessment. Overall, in 1000 screened patients, 90 screened positive and required further assessment, after which 25 qualified for brief intervention; after one year 2.6 (95% confidence interval 1.7 to 3.4) reported they drank less than the maximum recommended level. Conclusions Although even brief advice can reduce excessive drinking, screening in general practice does not seem to be an effective precursor to brief interventions targeting excessive alcohol use. This meta-analysis raises questions about the feasibility of screening in general practice for excessive use of alcohol.